Расчет нагревательных и термических печей: справочник - Василькова С. Б. Софья Борисовна; Генкина М. М. Мария Марковна; Гусовский В. Л. Виктор Львович; Лившиц А. Е. Адольф Ефимович; Тымчак В. М. Вячеслав Михайлович (Москва, Металлургия, 1983)
Авт. указаны на обороте тит. л.